MORPHOLOGY OF NEURONS OF MOTIVE AND SENSIBLE SЕGMЕNTАRY CENTERS SPINAL CORD AFTER LONG THERMS HYPOKINEZIA AND PHYSICAL LOADING - Popel, S.L. (World of Medicine and Biology, 2013)
The objective of research was establishment of the hіstо-ultrastructure alteration of neurons of motive and sensible sеgmеntаry centers of spinal cord under act of a 15- and 30 multiple physical load medial aerobic power after 240 day's hypokinezia. Experiments have been made on 252 rats of line Wistar with a long therms hypokinezia and animals which were covered by physical load medial aerobic power. Histological specimens were stained with toluidin blue by Nissl’s method, electronmicroscopic slices were fixed with glutaraldehid, post-fixed with tetraoхyd osmium and contrasted plumbum citrate by Reynolds’. It is set that at of long duration hypokinezia there are the destructive changes of neurons of motive and sensible sеgmеntаry centers of spinal cord and surrounding micro blood vessels. There also has been revealed positive influence of application of the frequent physical load medial aerobic power on motion of regenerator processes and normalization of structure of neurons and blood vessels in different components of simple reflex arc in the dynamics of experiment.
Keywords: spinal cord; histological changes; ultrastructure; long therms hypokinezia; physical load